Knowledge, attitudes and practices on dengue fever at Kampung Masjid, Daerah Barat Daya, Pulau Pinang / Fasyanazirah Aini Azizan - Azizan, Fasyanazirah Aini (2016)
Dengue Fever is endemic in Barat Daya District. A study was conducted to determine the level of knowledge, attitude an practices regarding the dengue fever infection and dengue prevention among villagers in Kampung Masjid, Teluk Kumbar, under Barat Daya District, Penang. The cross-sectional survey was conducted to assess the level of knowledge, attitudes and practice concerning dengue. The level of knowledge of the villager was good. Out of 100 respondent, 98% had good knowledge on cause of dengue fever, 94% know about sign and symptom of dengue fever, 95% had knowledge on mode of transmission of dengue fever and 97% of respondent know the preventive measure on dengue. Even the respondent had good knowledge, the attitudes and practice is irrelevant with knowledge. Most of respondent belief that dengue is a serious disease and belief to seek treatment for dengue infection. Half of respondent think that to control the dengue is their own responsibility. Meanwhile, 43% of respondent think it government responsibility to control and prevent dengue fever. The level of villager practices was not in good term. Only few of villagers conducted good practices. The dengue fever remains a public health in this area. The villagers should apply the knowledge with the relevant attitudes and practices. Some studies belief that attitude and practices is effective way to control and prevent dengue fever case.